Analysis of feasibility and outcome of bedside percutaneous endoscopic gastrostomy versus open feeding gastrostomy in head injury patients - Balsarkar, Dharmesh (2023)
In the present study, 50 patients with severe head injury needing feeding procedures were analysed. Patients underwent open feeding gastrostomy (n = 25) and the other patients a bedside PEG (n = 25) randomly. Both the groups were similar in demographic deposition and head injury severity. Male preponderance was seen, in both groups as in our country males tend to undertake more outdoor activities and there is an increased incidence of alcohol consumption among males. (Table 1).